Kinetic properties of peroxidase enzyme from chard (beta vulgaris subspecies cicla) leaves - Bursal, Ercan (My University, 2013)
Peroxidases are heme containing enzymes that are produced by a number of organisms. A plant peroxidase was purified from leaves of chard (Beta vulgaris subspecies cicla) by ammonium sulphate precipitation, dialyses, and CM-sephadex cation exchange chromatography. Purification fold was approximately 36 with 14.4% yield. Optimum pH, optimum temperature, optimum ionic strength, and stable pH values of purified enzyme were determined for the guaiacol substrate. Michaelis constant (KM) and maximum rate (Vmax) values were determined from the Lineweaver-Burk graph for pyrogallol and guaiacol substrates. Phenolic and flavonoid contents in chard that connected with antioxidant properties were determined as 17.5 ?g (GAE/mg extract) and 11.7 ?g (QE/mg extract), respectively. In conclusion, chard is shown to be a novel rich source of phenolic antioxidants and has a high peroxidase activity. © 2013 Copyright Taylor & Francis Group, LLC.
Keywords: Antioxidant enzymes; Chard; Chromatography; Peroxidase; Purification